Laying the Exegetical Foundations of the Reformed Tradition: Zwingli's Covenantal Reading of Genesis - Hildebrand, Pierrick (Reformed theological review, 2024)
This paper argues that Zwingli gained crucial exegetical insights during his lectures on the book of Genesis that made him the founder of covenant theology in the Reformed tradition, a theology based on the hermeneutic and redemptive-historical unity of the Old and New Testaments. Those lectures were held in the mid-1520s at the newly founded biblical-theological seminary in Zurich, almost nine years after Zwingli's conversion to sola scriptura and two years after the Reformation was introduced in the city. In particular, this article explores passages where the Zurich Reformer explicitly referred to a single covenant made with Adam, Noah, Abraham, and Moses that aligns with the new testament of Christ.